2012
DOI: 10.1016/j.jsams.2012.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Dose response relationships between physical activity, walking and health-related quality of life in mid-age and older women

Abstract: Background Although physical activity is associated with health-related quality of life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 12 publications
7
18
0
Order By: Relevance
“…Similar to our findings, Heesch et al 35 found that middle-aged women who approached, met, or exceeded PA recommendations reported greater vitality than those women who were sedentary or who completed very low to low amounts of total PA when PA was self-reported. 10,33<35 Specifically, our data show a stronger association of PA with prior month frequency of energy feelings (ie, SF-36 vitality scores) than with prior week intensity of energy feelings (POMS-SF vigor scores).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, Heesch et al 35 found that middle-aged women who approached, met, or exceeded PA recommendations reported greater vitality than those women who were sedentary or who completed very low to low amounts of total PA when PA was self-reported. 10,33<35 Specifically, our data show a stronger association of PA with prior month frequency of energy feelings (ie, SF-36 vitality scores) than with prior week intensity of energy feelings (POMS-SF vigor scores).…”
Section: Discussionsupporting
confidence: 91%
“…15 Face validity is illustrated by the strong prospective associations between this measure and a range of outcomes, including mental health, cardiovascular disease, and health-related quality of life. 28,[36][37][38] Furthermore, we show good agreement between self-reported and measured weight and height in the ALSWH. 18 Another limitation is that the women whose data were included had a healthy BMI at baseline so that we could assess the effects of PA on becoming overweight or obese.…”
Section: Discussionsupporting
confidence: 60%
“…The difference of 542 steps per day observed at 2 months may have limited clinical significance. A recent review of walking studies of older adults identified an association between increases of 2,000 to 3,000 steps per day and increases in immune functioning, decreases in body mass index, and achievement of the Centers for Disease Control and Prevention–recommended 30 minutes per day of moderate or greater physical activity through walking alone, although the dose‐response relationships between steps per day and bone density of the hip and spine, markers of inflammation, and health‐related quality of life appear to be linear and without threshold.…”
Section: Discussionmentioning
confidence: 99%